Innovation in Educational Management Leverages Technology and New Approaches to Increase Efficiency and Effectiveness - Hutapea, Samlihot; Antonius, Choir (Edumaniora : Jurnal Pendidikan dan Humaniora, 2023)
Education is an important foundation in the sustainable development of society, however, to ensure a quality education system, education management must continue to evolve with the times. Innovation in education management is crucial, especially in utilizing technology and new approaches to increase efficiency and effectiveness. This research aims to explore various innovations in education management that utilize new technology and approaches, as well as to analyze their impact on the efficiency and effectiveness of the education system. The research method used is a qualitative approach using observation, interview and document analysis techniques. Information obtained from educational practitioners, administrators, and educational technology developers is used to construct a comprehensive understanding of innovation in educational management. The research results show that innovations such as technology-based learning management systems, educational analytics, adaptive learning, and collaborative platforms have made significant contributions to increasing administrative efficiency, improving student learning experiences, and improving teaching quality. In this context, it is important to acknowledge the challenges that may arise, such as access to technology, the need for ongoing training, and issues of privacy and data security. However, the benefits offered by innovation in educational management far outweigh these challenges.